TRADISI PABUNCINGAN JERO DONG DING DI DESA PAKRAMAN MUNCAN, KECAMATAN SELAT KABUPATEN KARANGASEM - Ida Ayu Dwidyaniti Wira (Sanjiwani: Jurnal Filsafat, 2019)
Tradition Pabuncingan Jero Dong Ding is one form of religious traditions god yadnya devoted presented to Ida Sang Hyang Widhi Wasa conducted with the purpose of applying the fertility presented to Ida Sang Hyang Widhi Wasa in his manifestation as Lingga (jero Dong) and Yoni (Jero Ding) ie aspect of God in the form Purusa-Pradana symbol of Lord Shiva and Goddess Parvati or Uma. Based on this analysis, be concluded as the following results: The process of implementation of the tradition Pabuncingan Jero Dong Ding in Pakraman Muncan divided into three stages: The process of making, the process Ngelinggihang and activities Pabuncingan Jero Dong Ding. The reason for the implementation of the tradition Jero Pabuncingan Ding Dong, in theology is to invoke presented to Ida Sang Hyang Widhi Wasa in manifestation of Lord Shiva and Goddess Uma, in the mythology is based on the belief or confidence that developed in rural communities Pakraman Muncan.